1972
DOI: 10.1111/j.1471-4159.1972.tb01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Brain During Sleep and Wakefulness

Abstract: Abstract— The levels in brain of lactate, pyruvate, creatine phosphate, ATP, ADP and AMP were examined in sleeping and waking adult rats. The animals were monitored electrophysiologically and the biochemical measurements were made after approx. 25 min of sleep or wakefulness. The previous treatment of the animals had a marked effect on the levels of brain metabolites during sleep. In animals not acclimatized to the observation chamber, brain levels of lactate and pyruvate rose during sleep above those in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Our results are consistent with earlier work on whole brain energy metabolism during sleep-wake, showing an overall increase of high-energy phosphates during sleep (Van den Noort and Brine, 1970; Durie, 1978; Dworak et al, 2007). However, early work on brain energetics presented contradictory views on energy changes during sleep (Reich et al, 1972; Durie, 1978). Moreover, these studies did not parcellate brain into individual regions, did not measure ATP during a 24h light-dark cycle, and did not record sufficient electroencephalographic activity to distinguish wake, NREM and REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with earlier work on whole brain energy metabolism during sleep-wake, showing an overall increase of high-energy phosphates during sleep (Van den Noort and Brine, 1970; Durie, 1978; Dworak et al, 2007). However, early work on brain energetics presented contradictory views on energy changes during sleep (Reich et al, 1972; Durie, 1978). Moreover, these studies did not parcellate brain into individual regions, did not measure ATP during a 24h light-dark cycle, and did not record sufficient electroencephalographic activity to distinguish wake, NREM and REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…On a daily basis rats feed less during the 12 h of light period as they sleep most of the time. Although cerebral energy levels are observed to be restored [12, 23, 24], the body weight shows a decrease during the resting period of rats. These findings support the assumption that anabolic processes within the brain occur predominantly during sleep [25], whereas peripheral anabolism is likely to occur during wakefulness and is associated with food consumption [26].…”
Section: Discussionmentioning
confidence: 99%
“…The three most frequently cited investigations [23-251 concentrated on brain tissue (which may be the exception to other tissues in having a need for restitution during sleep). These three studies demonstrated increases in energy charge from waking to sleep, with one [24] observing that acclimatization of animals to the laboratory setting reduced this increase to insignificance. Another [25], a preliminary report for which no further details have been published, found relatively large energy charge increases in brain and muscle during sleep.…”
Section: Cellular Energy Charge and Sleepmentioning
confidence: 94%